The Mediating Effect of Knowledge Sharing on Interpersonal Trust and Job Satisfaction of Creative Industry in East Java - Noerchoidah .; Mochamad Mochklas; Ratih Indriyani; Bisma Arianto (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2022)
The purpose of this study is to analyze the implication of multivariate relationship among interpersonal trust, knowledge sharing and job satisfaction in creative industry in East Java. This research uses 168 employees as respondents in order to test hypothesis. Data are processed using Partial Least Square (PLS) model. Empirical analysis shows that there are positive and significant relationships between interpersonal trust and knowledge sharing, knowledge sharing toward job satisfaction, also between interpersonal trust and job satisfaction. Furthermore, the result of this study shows that knowledge sharing acts positively as mediating variable between interpersonal trust and job satisfaction